Comparative studies between public and private Islamic schools in the era of globalization - Umi Kultsum; Muhammad Abrar Parinduri; Abdul Karim (Institute of Advanced Engineering and Science, 2022)
The problem of decentralization is one of the main problems in madrasa modernization and independent learning. This is due to the difficult coordination and expensive learning processes being experienced. Therefore, this study aimed to determine the impact of the educational policy implementations on madrasa, with the existence of regional autonomy in Serang and Pandeglang Regencies, Indonesia. This qualitative study involved 10 participants, which contained district madrasa heads and supervisors, institutional managers, education staff, and teachers in Serang and Pandeglang. The utilized instruments were the interview protocol and observation sheet, with the data analysis being obtained through the Huberman and Miles's technique. This included reading, meaning, and data developed within the framework of the historical and ethnographic approach analysis. The results showed that there was no difference in the curriculum between public and private Islamic schools under the local government. The advantage was also observed for regional autonomy, regarding the emergence of superior, exemplary, regular, and vocational madrasas, respectively. However, the disadvantage of this policy was the difficulty in improving the quality of madrasa institutions, funding, and education personnel. These results indicated that all parties should contribute and supervise the implementation of autonomous education, to optimize the goals of each madrasa and achieve independent learning. Explicit rules are also needed regarding the understanding of discriminatory decentralization policies, especially in madrasa and other educational institutions.